The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/00207450701591065
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphic Evidence for Night-Time Hyperkinesia in Parkinson’s Disease

Abstract: Parkinson's disease is a common motor disorder that not only leads to motor symptoms but also autonomic dysregulation, mental changes, sensory disturbances, and sleep disorders such as increased daytime sleepiness and sleep fragmentation. The aim of this study was to find out how the daytime and night-time motor activity levels in individuals without motor disorders differ from patients with Parkinson's disease. Daytime and night-time motor activity levels in 17 PD patients and 69 controls were measured for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A lower frequency of turning-over events in bed in patients with PD was also reported by Laihinen and colleagues 25. By contrast, elevated nocturnal activity level and an increased proportion of time with movement have been reported in PD as well 23 24. The latter findings are based on the quantification of an activity level.…”
Section: Discussionmentioning
confidence: 65%
“…A lower frequency of turning-over events in bed in patients with PD was also reported by Laihinen and colleagues 25. By contrast, elevated nocturnal activity level and an increased proportion of time with movement have been reported in PD as well 23 24. The latter findings are based on the quantification of an activity level.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have placed the accuracy of actigraphy at 0.85 agreement with polysomnography, a value which was within the acceptable range for longitudinal data collection (Wright et al, 2000). In addition, many studies have now shown that actigraphy is an appropriate method for measuring sleep quality in PD (Nass & Nass, 2008;Perez-Lloret et al, 2009;Stavitsky, Saurman, McNamara, & Cronin-Golomb, 2010). Although parkinsonian daytime tremor (Hoehn & Yahr, 1967) 2.0 (.70) 1.8 (.62) -…”
Section: Methodsmentioning
confidence: 97%
“…Schlesinger et al (2009) have shown that actigraphy is a reliable method for measuring fluctuations in rest tremor severity during a mind-body intervention. Nass and Nass (2008) have also shown that actigraphy can be used to differentiate Parkinson’s patients from healthy controls.…”
Section: Case Studymentioning
confidence: 99%